Climate Changes on the Amount of Rain and Temperature from 1990-2018 in Madaba, Jordan using Geographical Information Systems - Rawashdeh, Shatha; A Thneibat, Ahmed; Aladwan, Zubeida; Taran, Ayed; Alrababah, Abdallah (Indonesian Journal of Geography, 2024)
Climate change is an important topic requiring thorough study due to the importance and increasing impact on the various environmental and human systems. Therefore, this study aimed to clarify the changes observed in the minimum and maximum temperatures, as well as the calculation of rainfall rates during the period spanning 1990 to 2018 in the governorate of Madaba. The amount of rain as well as the average minimum and maximum temperatures were examined through annual, seasonal, and monthly analyses. The comparison results from 2018, 2010, 2000, and 1990 showed that there was an increase in the seasonal, annual, and maximum temperatures for the month of June reaching about 1.51 °C. The month of July and Shahrab reported an elevation of 1.06 °C and 1.26 °C with an annual increase in maximum temperatures of 1.44 °C. Similarly, rainfall rates decreased by 0.05 mm between 1990 and 2018, hence legislative laws were enacted against individuals contributing to climate change. This started with individuals practicing waste and garbage burning, as well as developing unified programs and plans to address the consequences.